1999
DOI: 10.1099/0022-1317-80-6-1495
|View full text |Cite
|
Sign up to set email alerts
|

Variation within the glycoprotein B gene of human cytomegalovirus is due to homologous recombination.

Abstract: Human cytomegalovirus (HCMV) strains can be classified into different glycoprotein B (gB) genotypes. In a previous study, frequent intragenic variation of the gB gene was shown. The aim of this study was to analyse whether gB variation was due to homologous recombination. The gB gene of DNA extracts derived from the peripheral blood leukocytes of 14 immunosuppressed patients was amplified by PCR and cloned. Three variable sites of gB were analysed by restriction fragment analysis and DNA sequencing and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 27 publications
2
47
2
Order By: Relevance
“…Evidence for strain recombination has also been observed among clinical isolates of human herpesvirus 8 (34), cytomegalovirus (18), and Epstein-Barr virus isolates (28,45). As such, homologous recombination appears to be a general feature of human herpesvirus evolution and an important mechanism for maintaining genetic diversity among human herpesvirus strains.…”
Section: Discussionmentioning
confidence: 97%
“…Evidence for strain recombination has also been observed among clinical isolates of human herpesvirus 8 (34), cytomegalovirus (18), and Epstein-Barr virus isolates (28,45). As such, homologous recombination appears to be a general feature of human herpesvirus evolution and an important mechanism for maintaining genetic diversity among human herpesvirus strains.…”
Section: Discussionmentioning
confidence: 97%
“…Clinical isolates of human cytomegalovirus (HCMV) show significant sequence diversity by RFLP analysis and sequencing of selected ORFs (10,13,15,43). Furthermore, it is difficult to assign HCMV isolates into strain groups, due to a relatively high frequency of recombination, indicated by variation of gB via intragenic recombination and relative rarity of genetic linkages between nine separate variable loci (20,48). Similarly, a study of sequence variation between clinical isolates for genes within the Us region of HSV-1 (gG, gI, and gE) concluded that homologous recombination (intra-and intergenic) was a common event (40).…”
Section: Discussionmentioning
confidence: 99%
“…Other factors that could affect melting temperature, such as the primer and probe purification, DNA extraction, and PCR conditions, were similar in Schaade's and our study except for a difference in the annealing temperature (58 and 55°C, respectively). Genetic heterogeneities of CMV glycoprotein B gene from patients with different clinical backgrounds were previously described (12,34). While all of the patients in our study had solid organ transplantation, Schaade et al did not specify the clinical histories of their patients.…”
Section: Discussionmentioning
confidence: 99%